Correlations of morphological features and surgical management with clinical outcome in a multicentre study of 241 phyllodes tumours of the breast. Issue 6 (22nd March 2021) - Mihai, Raluca; Callagy, Grace; Qassid, Omar L; Loughlin, Mark O; Al‐Hilfi, Lena; Abbas, Areeg; Campora, Michela; Hodi, Zsolt; Ellis, Ian; Lee, Andrew H S; Rakha, Emad A
Abstract : Aims: Phyllodes tumours (PTs) represent an unusual but complex group of breast lesions with a tendency to recur locally and, less commonly, metastasise. On core biopsies, their appearances can be difficult to discriminate from those of other fibroepithelial lesions, which may compromise their surgical management. The aims of this study were to assess the preoperative diagnosis of PTs and to evaluate the impacts of surgical management and morphological features on their behaviour. Methods and results: We combined datasets from three centres over two decades, including core biopsies, excision specimens, and follow‐up. Core biopsy results were compared with final excision specimens. The relationships of surgical procedure and morphological features with local recurrence (LR) and metastasis were assessed. Two hundred and forty‐one PTs were studied. Core biopsy resulted in a diagnosis of possible or definite PT in 76% of cases. Malignant tumours were more likely to be larger, occurred at an older age, and were surgically more challenging, with difficulties being encountered in achieving negative margins. There were 12 cases (5%) that showed LR alone, and another six cases (2.5%) that had distant metastases. Morphological features associated with adverse outcome were grade of PT, increased mitotic counts, necrosis, infiltrative margins, stromal atypia, and heterologous components. Both LR and metastatic behaviour correlated with larger size and distance to margins. Conclusions: Our results suggest that excision margins have a significant impact on LR of PT, whereas metastatic behaviour is influenced by tumour biology. We add to the evidence base on histological features of tumours that contribute to long‐term outcomes of PT patients. Abstract :